Reshaping Urbanization in Rwanda : Internal Migration in Rwanda - World Bank Group (World Bank, Washington, DC, 2017)
The objective of this report is to inform the government’s policies and strategies on urbanization as a driver of economic development, job creation, and poverty reduction. Note two examines internal migration in Rwanda, which is a recent phenomenon and remains fairly limited, with less than 10 percent of the population changing their district of residence in the three years between 2011 and 2014. Rural‐to‐urban migration has increased slightly as a share of internal migration, and with internal migration increasing overall, the absolute number of people moving from rural to urban areas has grown. The spatial disparities in living standards offer a compelling motivation for people in lagging areas to move closer to economic density. This note takes a closer look at the scale and nature of internal migration in Rwanda. This note is organized as follows: section one gives introduction. Section two presents the scale and pattern of internal migration, focusing particularly on rural‐to‐urban migration and the secondary cities. Section three sketches the characteristics of migrants, focusing on push and pull factors and disaggregating by type of migration. The final section four concludes.